How do Universities Make Progress? Stakeholder-Related Mechanisms Affecting Adoption of Sustainability in University Curricula - De Lange, Deborah E. (Journal of business ethics, 2013)
This paper develops a theoretical model to explicate stakeholder-related mechanisms that affect university adoption of sustainability in curricula. This work combines stakeholder and institutional theories so as to extend both. By examining change in the university context wherein there is confusion about sustainability adoption, this research adds to previous institutional theory focusing on strongly contested practices, primarily in the for-profit firm setting. Sustainability is a transformational challenge and may be adopted reactively or proactively. Also, stakeholder theory is extended in a mixed profit and non-profit context. Propositions suggest how the extent of embeddedness affects an organizations’ selection of stakeholders, consequently affecting the type of adoption. This facilitates a greater understanding of why two competing definitions of stakeholders may operate. Moreover, extrinsic and intrinsic motivations are discussed as affecting adoption in different ways. A responsible leader organization is newly defined and intrinsic motivation is proposed as underlying its choice of the widest set of stakeholders leading to broad, proactive adoption.